Advances in High-Pressure Techniques for Geophysical Applications 2005
DOI: 10.1016/b978-044451979-5/50006-5
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of elastic and structural properties under simulated mantle conditions using multi-anvil device MAX80

Abstract: An ultrasonic interferometry high-pressure set-up for elastic wave velocity measurements under simulated Earth's mantle conditions has been developed. A DIA-type multi-anvil apparatus MAX80 permanently located at HASYLAB, Hamburg, Germany for X-ray diffraction (XRD) under in situ condition was equipped for simultaneous ultrasonic measurements. Two of the six anvils were equipped with lithium niobate P-and S-wave transducers of 33.3 MHz natural frequency. The pressure and temperature limits of the high-pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 29 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…Knoche et al (1997Knoche et al ( , 1998) had a hot isostatically pressed forsterite sample between two platinum buffer rods. Consequently, the condition mentioned can be a good approximation for high-strength samples, as it was also the case in our experiments with San Carlos olivine, anorthite, clinoenstatite, and Calibration based on a primary pressure scale in a multi-anvil device 433 quartz (see Mueller et al (2004), page xxx, this volume), but not if a ductile sample is taken into account.…”
Section: Determination Of Sample Lengthmentioning
confidence: 92%
See 2 more Smart Citations
“…Knoche et al (1997Knoche et al ( , 1998) had a hot isostatically pressed forsterite sample between two platinum buffer rods. Consequently, the condition mentioned can be a good approximation for high-strength samples, as it was also the case in our experiments with San Carlos olivine, anorthite, clinoenstatite, and Calibration based on a primary pressure scale in a multi-anvil device 433 quartz (see Mueller et al (2004), page xxx, this volume), but not if a ductile sample is taken into account.…”
Section: Determination Of Sample Lengthmentioning
confidence: 92%
“…The sample is surrounded by rings made from boron nitride or glass ceramics for electrical insulation and as a quasi-hydrostatic pressure transmitting medium. Further details of the apparatus are described by Mueller et al (2004) on page xxx, this volume and also by Mueller et al (2002). …”
Section: Techniques Methods and Materials Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments demonstrated that maximum pressures at least 25% higher compared to the standard MAX80 confi guration are easily achievable while using prefabricated gaskets. Further benefi ts are a reduced number of blowouts, i.e., decompression of the cell assembly by gasket failure, and higher X-ray intensity at peak pressures due to the larger gap width between the anvils (Mueller et al, 2005a).…”
Section: Pressure Generationmentioning
confidence: 99%
“…Otherwise the intense X-rays would destroy the CCD (Charge-Coupled Device) chip of the camera and would cause radiation damage in the optical glass of the lenses. The limit of the optical resolution is determined by the wavelength of green light of ~0.5 μm and the aperture of the objective of less than 0.5 to a total of ~1 μm (Mueller et al, 2005a). The minimum object distance is a strongly limiting factor for the selection of useful objectives.…”
Section: X-radiographymentioning
confidence: 99%